Kajian Perempuan Pesisir dalam Mendukung Konservasi Sumber Daya Pesisir di Kabupaten Raja Ampat - Handayani - (Fakultas Perikanan dan Ilmu Kelautan, 2011)
The Regency Raja Ampat is an archipelago area with great of coastal resources potency. These potencies affected by human activity, and need to be followed with development strategy of coastal resources. One of the social potency development is woman of coastal area. Research objectives are to analyse social factors woman of coastal area and issues expanding in management of coastal area resource. The result from this research woman of dominant coastal area and comprehend information concerning coastal area resource conservation besides woman of coastal area have readiness, caring and compliance to conservation. Woman in coastal area have enteraction on the continuation of the coastal resources.